Совершенствование технических средств и технологии отбора проб грунта при бурении геотехнических скважин с плавучих самоподъемных установок на шельфе Черного моря - Каракозов, А.А.; Калиниченко, О.И.; Зыбинский, П.В.; Парфенюк, С.Н.; Хохуля, А.В.; Комарь, П.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Results of development of technologies and the equipment for drilling geotechnical wells during engineering-geological researches on a shelf are presented. Constructive schemes of the equipment, its characteristics and technological schemes of operation which have been tested at work on Subbotin’s oil-and-gas deposits in Black sea are presented too. Estimation of the influence of configurations of a bottom of a drill string on drilling mechanical speed has been done for improvement of technology of drilling by hummer tools. Some results of modeling are presented, the choice of configurations and recommendations on their use is proved.